On the optimal model configuration for aerodynamic modeling of open cargo railway train - Golovanevskiy, Vladimir; Chmovzh, V.; Girka, Y. (Elsevier BV, 2012)
This study is concerned with the optimal model configuration for aerodynamic modeling of long open cargo railway trains. Frontal air drag of several train configurations was studied using numerical modeling and physical i.e. wind tunnel testing of 1:40 scale railcar models in a range of cross-wind angles. In a long train, the locomotive and the last railcar influence the aerodynamic characteristics of the first three and the last three railcars only. Aerodynamic performance of all other railcars in the long train is similar and can be represented by two inner-train railcars only. A model train configuration combining the shortest computation time with the lowest experimental error was determined from numerical modeling and this was then used for wind tunnel testing. It has been shown that, for long open cargo railway trains the model consisting of six railcars with two streamlined bodies is the optimal configuration, with both the numerical modeling and wind tunnel testing results in good agreement.